Developing A Story Busy Book of Ant and Grasshopper as Teaching Vocabulary Media to the EYL - Sri Wahyuni (Language-Edu, 2021)
The main goal of the research is to develop a story busy book of Ant and Grasshopper for second grade students to teach the vocabulary for the children of SDN Merjosari 2 Malang. The research is classified into fundamental research and development. This research involved 8 steps. They conducted a need analysis, wrote the course grid, designed, assessed, revised, implemented, evaluated and revised the media and produced the final media. The study involved 24 second grade students from SDN Merjosari 2 Malang. Questionnaires provided quantitative data for this study, while observation provided qualitative data. The experts of media, contents, busy book, and English teacher were asked to complete the surveys. Simple descriptive statistics were used to analyze the quantitative data, while narrative analysis was used to analyze the qualitative data.The study product is a story busy book of Ant and Grasshopper that can be used to teach vocabulary to the EYL students. Based on the assessment of a content expert, media expert, busy book expert, English teacher and students, it has been determined that the busy book of Ant and Grasshopper is appropriate for media use in learning vocabulary. Based on the content expert's assessment, the percentage rating is 75. Additionally, the media expert assigned a percentage score of 86.26 %. The percentage score is 88.35 % based on the media expert's assessment. The English teacher assigned a percentage score of 96.8 %. As a consequence, the story busy book of Ant and Grasshopper is an outstanding and practical media for learning vocabulary to the EYL. The percentage score is thus 89.7 % based on the students' responses. This indicates that the story busy book of Ant and Grasshopper was an excellent alternative media to teach vocabulary. According the data, the story busy book of Ant and Grasshopper is an effective media for increasing students' attention spans, providing constant repetition, and assisting students in better comprehending the vocabulary.